Kompetensi, Sikap Kerja, dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Perumahan dan Permukiman Kabupaten Aceh Tengah - Darmawansyah Putra; Teuku Muhammad Nur; Wirda Inayati (Singkite Journal, 2025)
The study aimed to analyze the contribution of competency, work attitude, and work environment aspects to improving employee performance. The study was conducted on employees of the Housing and Settlement Service of Central Aceh Regency. The study employed a quantitative associative approach, supported by path analysis. The results revealed: (1) there is a causal relationship between the three causal factors: competency, work attitude, and work environment, with a moderate categorization. (2) Employee competency, work attitude, and work environment significantly influence employee performance by 56.24%, while work  attitude contributes 57.21%, and the work environment 36.98%. (3) Simultaneously, competency, work attitude, and work environment contribute positively to improving employee performance by 72.2%.